2019
DOI: 10.5935/1518-0557.20190007
|View full text |Cite
|
Sign up to set email alerts
|

The elimination of apoptotic sperm in IVF procedures and its effect on pregnancy rate

Abstract: Objective: To identify the effect of apoptotic sperm elimination with MACS in patients that require IVF. Methods: An experimental, cross-sectional, descriptive, prospective and non-blinded study of diagnostic tests performed in patients who required IVF and ICSI from July 2011 to July 2012. Ninety-two couples participated according to the treatment administered to the semen sample; in the control group: the samples were subjected only to density gradients before ICSI, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…High levels of early-stage sperm apoptosis have also been suggested to play a role in recurrent pregnancy loss 23 . It has also been demonstrated that the use of apoptotic sperm removal plays a signi cant role in improving fertilization rate and rates of clinical pregnancies when combined with the use of good quality donor oocytes 20 . The value of removing apoptotic sperm resides in the fact that they may still be able to fertilize an oocyte, particularly during an ICSI treatment, as they often present without morphological abnormalities.…”
Section: Hybrid Sperm Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…High levels of early-stage sperm apoptosis have also been suggested to play a role in recurrent pregnancy loss 23 . It has also been demonstrated that the use of apoptotic sperm removal plays a signi cant role in improving fertilization rate and rates of clinical pregnancies when combined with the use of good quality donor oocytes 20 . The value of removing apoptotic sperm resides in the fact that they may still be able to fertilize an oocyte, particularly during an ICSI treatment, as they often present without morphological abnormalities.…”
Section: Hybrid Sperm Selectionmentioning
confidence: 99%
“…One such marker is the externalized membrane protein phosphatidylserine, which is an indicator or early-stage apoptosis in sperm. It has already been proven that the proportion of early apoptotic sperm cells in raw semen can reach over 20% 19 , and that eliminating apoptotic sperm using annexins correlates to an improvement in embryo quality 20 and a further decrease in sperm DNA fragmentation which is directly correlated to apoptosis 56 . High levels of early-stage sperm apoptosis have also been suggested to play a role in recurrent pregnancy loss 23 .…”
Section: Hybrid Sperm Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, using a combination of mechanisms for sperm selection may provide more fecund sperm, particularly for ICSI. One mechanism involves the tagging and removal of apoptotic sperm using Annexin V. The proportion of early apoptotic sperm cells in raw semen has been shown to reach over 20% 21 , and it has been reported that eliminating apoptotic sperm using annexins correlated with an improvement in embryo quality 22 . Annexin A5 (AAV) is an example of one such apoptotic marker that binds to phosphatidylserine externalized in apoptotic cells 22 .…”
Section: Introductionmentioning
confidence: 99%